(3QSGdI aj GdcdjGJ GdNeSs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg hdeG Jhba eYQaJgG Ydi eYQaI GdbVGjG ceG Cf Gdbhd GdTGQM eHGOF jJhba YdjgG hjLH JbOjegG Ydjg hgj eHGMK GdcdjGJ GdNeS JQcJ GdeYQa efgG cPdc ddMLI eHGOF (B...s
(3BNQgG (B:s
... (3hgPG GdLhGH eQOhO dCf GdTjN GdQFjS bO UQM aj GdTaGA HCf GdJUOjb HhLhO GdehVhY ef GdeHGOF GdJUOjbjI adG jchf CjVG LRGA Ydi MOI Hd efOQL aj GdeHGOF GdJUOjbjI hGddg CYde HGdUhGHs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs